Vaginal Misoprostol for Cervical Priming before Gynaecological Procedures on Non Pregnant Women - Saha, Shyama Prasad (Qassim University, Kingdom of Saudi Arabia, 2007)
BACKGROUND: Misoprostol has been extensively researched for its use in obstetrics and has proved to be a very effective cervical softening agent before termination of pregnancy. The beneficial effects on cervical ripening may make misoprostol a desirable agent for helping cervical dilatation on non pregnant women also. The objective is to study the efficacy of preoperative vaginal application of misoprostol as cervical priming agent before gynaecological procedures on non pregnant women. METHODS: DESIGN: A randomized controlled trial. SETTING: Department of Gynaecology and Obstetrics of two medical colleges. PARTICIPANTS: 468 non pregnant pre-menopausal nulli-parous or parous women scheduled to have diagnostic D&C or diagnostic hysteroscopy operations. INTERVENTIONS: 400 mcg intravaginal misoprostol (229 women) in the study group and 400 mg intravaginal metronidazole as placebo (231 women) in control group. OUTCOME MEASURE: The main outcome measures were baseline cervical width at the beginning of the procedures, the number of women who required further cervical dilatation, time taken for dilatation, side effects and other complications. RESULTS : Base line cervical width in the study group was significantly higher than control group (4.6±0.8 mm vs. 3.8±0.7 mm, p < 0.0001). 141 (61.57%) cases required further cervical dilatation in the study group compared to 206 (89.18%) in the control group (p < 0.0001). Time taken for further cervical dilatation was significantly lower in the study group compared to control group (48.3±18.4 sec vs. 68.6±17.3 sec, p < 0.0001). Cervical injury and uterine perforation occurred in 12 and 3 women respectively in the control group compared to 1 and 0 women respectively in the misoprostol group. Two most common side effects of vaginal misoprostol were mild lower abdominal pain (21%) and slight vaginal bleeding (09.2%) which were within tolerable limit. CONCLUSION: Preoperative vaginal application of misoprostol before gynaecological procedures on non pregnant women decreases the cervical resistance, facilitates the cervical dilatation and operative procedures minimizing cervical or uterine injuries.